Fluorine-doped Fe2O3 as high energy density electroactive material for hybrid supercapacitor applications - Karthikeyan, Kaliyappan (2014)
Nanostructured α-Fe2O3 with and without fluorine substitution were successfully obtained by a green route, that is, microwave irradiation. The hematite phase materials were evaluated as a high-performance electrode material in a hybrid supercapacitor configuration along with activated carbon (AC). The presence of fluorine was confirmed through X-ray photoelectron spectroscopy and transmission electron microscopy. Fluorine-doped Fe2O3 (F-Fe2O3) exhibits an enhanced pseudocapacitive performance compared to that of the bare hematite phase. The F-Fe2O3/AC cell delivered a specific capacitance of 71 F g−1 at a current density of 2.25 A g−1 and retained approximately 90 % of its initial capacitance after 15 000 cycles. Furthermore, the F-Fe2O3/AC cell showed a very high energy density of about 28 W h kg−1 compared to bare hematite phase (∼9 W h kg−1). These data clearly reveal that the electrochemical performance of Fe2O3 can be improved by fluorine doping, thereby dramatically improving the energy density of the system.